Naproxen degradation test to monitor Trametes versicolor activity in solid-state bioremediation processes - Rodríguez Rodríguez, Carlos E. (2010)
The white-rot fungus Trametes versicolor has been studied as a potential agent for the removal of envi ronmental pollutants. For long-time solid-phase bioremediation systems a test is required to monitor the metabolic status of T. versicolor and its degradation capability at different stages. A biodegradation test based on the percentage of degradation of a spiked model pharmaceutical (anti-inflammatory naproxen) in 24 h (ND24) is proposed to monitor the removal of pharmaceuticals and personal care products in sewage sludge. ND24 is intended to act as a test complementary to ergosterol quantification as specific fungal biomarker, and laccase activity as extracellular oxidative capacity of T. versicolor. For samples col lected over 45 d, ND24 values did not necessarily correlate with ergosterol or laccase amounts but in most cases, they were over 30% degradation, indicating that T. versicolor may be suitable for bioremediation of sewage sludge in the studied period.